Support network and social support for children with special health care need - Thaís Araújo Barbosa; Kamilla Milione Nogueira Reis; Gabriela de Oliveira Lomba; Gabriela Vilaça Alves; Patrícia Pinto Braga (Universidade Federal do Ceará, 2016)
Objective: to understand and identify the support network and social support from the perspective of families of children with chronic conditions. Methods: a qualitative study, with content analysis of 134 records, followed by ten semi-structured interviews. Results: the analysis has revealed that the primary caregiver, the mother, participates in a network of limited support, only with the help of her husband, children, grandparents and the child´s godparents. They also have a social network through a multidisciplinary team, which in some cases is not effective. Conclusion: families have a deficient and limited support network and the demand for care rely only on the support of the husband, grandparents, children, and godparents. Social networking refers to the philanthropic institutions, while the aid of public service, basic health unit is basic.